DEIKSIS TEMPAT DAN WAKTU DALAM NOVEL “DOMPET AYAH SEPATU IBU” KARYA J.S KHAIREN - Masluhatul Khairiyah (SulukAksara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research examines the Deixis Study in the Novel " Dad's Wallet Mom's Shoes " by J.S Khairen. The formulation of the problem in this research is what the form of deixis is in the novel Dad's Wallet Mom's Shoes by J.S Khairen. Looking at the problem formulation, of course there is a research objective, namely explaining the form of deixis in the novel Dad's Wallet Mom's Shoes by J.S Khairen. This research is a descriptive qualitative research. This research focuses on the study of Persona Deixis, Space and Time in the dialogue of the novel Dad's Wallet Mom's Shoes by J.S Khairen. The use of Persona deixis in the novel Dad's Wallet Mom's Shoes by J.S Khairen can be seen from the examples of deixis found in the novel as follows: (1) Persona Deixis: me, me, -my, my-, we, us, you, -mu, you, you guys, he, -his, he, they. (2) Space Deixis: there, here, there, this way, where, that, this, there. (3) Time Deixis: later, tomorrow, past, now, yesterday, the day before yesterday, earlier. The total number of peronsa deixis in the novel Dad's Wallet Mom's Shoes by J.S Khairen is 534 data. For time deixis, 58 data were found. Meanwhile, for spatial deixis, 58 data were found.